A case of pediatric AIDS in Dr. Sutomo Hospital Surabaya, Indonesia - Ismoedijanto Ismoedijanto; Rosanti Yustina; Rahayu Tri Lestari; Hidayat Burhan (Paediatrica Indonesiana, 2001)
We report a 2-year old girl who suffered from HIV. The diagnosis was based on history, clinical findings, andlaboratory work-up. Suspicion of the presence of HIV was started when the girl continued to have wasting syndrom e withseveral focal infections unresponsice to ordinary treatment. The patient past away following severe diarrhea and apparentlysepsis.